Carbon nanotubes coated with phosphorus-nitrogen flame retardant and its application in epoxy thermosets. Issue 17 (22nd November 2019) - Xin, Fei; Zhai, Congcong; Guo, Chao; Chen, Yu; Qian, Lijun
ABSTRACT: Carbon nanotubes coated with phosphorus-nitrogen flame retardant (PDAP-CNTs) were produced. The compositions and structures of PDAP-CNTs were systematically characterized, and the flame retardancy of PDAP-CNTs/EP composites were also tested. The results indicated that PDAP-CNTs demonstrated excellent flame retardancy performance on the flame-retardant EP composites (FR-EP), incorporation of 5.0wt% PDAP-CNTs improved the LOI values of EP from 26.0% to 31.8% and reached UL-94 V-0 classification. The analysis of flame-retardant mechanism indicating the flame-retardant ability of PDAP-CNTs was ascribed to the synergism of the phosphorus-nitrogen containing coating layer (PDAP) and CNTs. GRAPHICAL ABSTRACT: